Mentoring millennials in an Asian context : talent management insights from Singapore - Lim, Paul; Parker, Andrew (Emerald Publishing Limited, 2020)
Millennials make up 25% of Asians. As this huge demographic surges towards becoming a substantial contributor to Asia's workforce, organisations continue to face engagement and retention challenges due to multi-generational workplace conflicts. Mentoring research in Western nations has consistently shown that mentoring brings tangible benefits to the organisation in the areas of job satisfaction, organisational commitment and employee retention, but would such observations apply to an Asian context? Taking Singapore as a point of reference, Mentoring Millennials in an Asian Context tackles this question head-on. It addresses both how millennials in Singapore perceive their mentors and how mentors can become better equipped for their mentoring. It identifies, analyses and offers solutions to existing problems such as inconsistent methods, a lack of mentoring knowledge and an urgent need to evolve with the times. For its 21st-century, region-specific approach, this book is an insightful read for HR academics and researchers, as well as C-Suite decision makers, senior managers and talent management coaches who wish to shape onboarding and mentoring policies for better engagement, retention and recruitment in preparation for the post-millennial generation in Asia.